Factors contributing to adoption and use of information and communication technologies within research collaborations in Kenya. (30th August 2016) - Muriithi, Petronilla; Horner, David; Pemberton, Lyn
Abstract : Use of information and communication technologies (ICTs) to support research work is becoming increasingly common. This study set out to establish how ICTs are being used to support collaborative research in Kenya, and identify factors within the ICT ecosystem that contribute to their adoption and use. A mixed methods research design, involving 248 academic scientists in 4 disciplines across 4 major Kenyan universities, was employed. We find little diversity in forms of ICTs used to support collaborative research within the studied population. Several factors affect adoption and use practices, including availability and access to ICT resources, nature of the work, national and institutional ICT and research environments and the social cultural practices of researchers. We explain our findings using Venkatesh et al.'s Unified Theory of Acceptance and Use of Technology model, which identifies four main constructs that affect adoption of technology such as performance expectancy, effort expectancy, facilitating conditions and social influence.